Synthesis of reduced graphene oxide nanosheets from sugarcane dry leaves by two-stage pyrolysis for antibacterial activity - Baskar Thangaraj; Pravin Raj Solomon; Nutthapon Wongyao; Mohamed I. Helal; Ali Abdullah; Sufian Abedrabbo; Jamal Hassan (Nano Materials Science, 2024)
Oxidative-exfoliation methods were in vogue in the production of rGO from graphite. Processing of such synthetic graphite needs high temperatures (≥2500 ​°C). Thus, such process is not cost-effective. The present study is made on the dry leaves of sugarcane (Saccharum officinarum) as an alternative raw material so as to be economical and environmentally benign. The dry leaves are subjected to two-step pyrolysis without any catalyst or reducing agent in far divergent temperatures to produce as prepared and acid treated rGOs. They were evaluated by UV–Vis., FTIR, XRD, Raman spectroscopy, TGA/DTG, BET, FESEM-EDS and TEM. The as prepared rGO has few layers with irregular and folded architecture whereas acid-treated rGO has thinly stacked crumpled sheets with many wrinkles on its surface. The prepared rGOs have multilayered graphitic structure due to the unique ratio between G and D bands. Acid treated rGO has poor thermal stability as compared to that of as-prepared rGO at high temperatures due to the variation in the oxygen-containing functional groups. Acid treated rGO has low antibacterial activity as compared to that of the as-prepared rGO due to the paucity of the functional groups.